Coronavirus (COVID-19) disease pandemic effect on the sports industry - Statistics & Facts - Gough, C. (Statista, 2020)
The 2019-20 coronavirus (COVID-19) pandemic that has swept across the globe in the last few weeks and months has not only had a significant impact on public health, society, and the economy as a whole, it has also wreaked havoc to the sporting calendar. In a bid to stem the spread of the virus, many professional and amateur leagues across all continents and sports took the unprecedented step to postpone or suspend their seasons on the advice of the CDC to avoid gatherings of large amounts of people.